EFEKTIVITAS PEMBERIAN TERAPI OKSIGEN 100% TERHADAP KADAR SATURASI OKSIGEN PADA PASIEN TERPASANG VENTILATOR YANG DILAKUKAN SUCTION - Liza Imelda Hanafi; Yesi " Hasneli; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract The action of suction can cause the hypoxemia which marked by reducing the oxygen saturation levels (SpO2) it causes the action of suction can be solved by oxygen therapy. This research aimed to know the effectiveness of giving 100% oxygen of  therapy  toward oxygenof  saturation levels on patients ventilator used which was done the suction at  Intensive Care Unit (ICU) room. The design of this research was quasy experiment with non-equivalent control group approach. Sample of this research was 30 persons with using technique of purposive sampling. Analysis of data in this research was invariant analysis for knowing the frequency of distribution and bivariate analysis used to test Wilcoxon and to test mann Whitney. The result of this research indicated the most of respondents who were at productive age (15-44 years old) as many as 11 persons (40,0%) and the gender of female as many as 16 persons (53,33%). The result of bivariate analysis indicated that  there was no difference between after and before giving 100% oxygen of therapy on patients ventilator used which were done the suction by using p value (0,065 )> a (0,05) on experimental group was found the difference significantly between patients saturation levels used ventilator at control group with p value  (0,001) < α (0,05). The difference of mean oxygen of saturation levels before and after intervention at experiment group and control group known that reduction of saturation oxygen levels in control group more than experiment group. The researcher recommended to the institution for can do the suctioning in accordance with the standard operating procedures (SOP). Keywords:Oxygen of saturation, oxygen of therapy, suction, ventilator